Effect of Dementia Prevention Program in Older Person based on Multicultural Way through Application to Enhance Cognitive Ability of Older Persons at Risk of Dementia, Narathiwat Province - Tohpaeroh, Muslin; Jaisomkom, Anyapaksorn; Piboonrungroj, Prasert; Tongnuang, Patcharawadee; E-tae, Waehaleemoh; Chehleh, Wanaisoh; Jehma, Rusya; Masaleng, Walliya (Princess of Naradhiwas University Journal, 2021)
This research is a one group pretest – posttest design type of quasi-experimental study aimed to compare the cognitive scores of the elderly at risk of dementia before and after using “Soong wai Maileum” application for prevention of dementia in elderly based on multicultural way. The samples of this study were 30 elderly at risk of dementia, aged 60 years and over living in Bangnak District, Narathiwat Province, selected by multistage random sampling. The experimental tool was “Soong wai Maileum” application which the program in the application consisted of 8 activities, required participation twice a week and took 60 minutes each time. Data was collected using a personal information questionnaire and the Mini-Mental State Examination-Thai 2002 test (MMSE-Thai 2002); it uses to screen sample groups and measure cognitive ability. The tool was verified its validity by experts and its reliability by Pearson’s correlation, received overall scores 0.95. Data were analyzed using descriptive statistics and paired t-test. The results of this study revealed that the average cognitive scores after participating in the program were significantly higher than before participating the prevention program. (t = 13.59, p <.000). The results of this research can be used as a guideline for enhancing cognitive function and further preventing dementia in elderly.